2013
DOI: 10.1093/humupd/dmt046
|View full text |Cite
|
Sign up to set email alerts
|

The combined human sperm proteome: cellular pathways and implications for basic and clinical science

Abstract: The analysis of the most complete sperm proteome available to date indicates the presence of several cellular protein pathways previously ignored in the male gamete. Confirming the activity of each of these pathways and understanding their biological significance will certainly boost the knowledge of human sperm and male fertility and infertility in the next years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
223
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(230 citation statements)
references
References 245 publications
7
223
0
Order By: Relevance
“…The use of genomic, transcriptomic and proteomic technologies significantly contributed to characterize and better understand the human sperm at the molecular level (Jodar et al, 2012;Kovac et al, 2013;Amaral et al, 2014a). However, metabolomics, the study of small and low molecular weight molecules that are products of metabolism, has not been greatly applied in the study and characterization of human sperm cells (Kovac et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of genomic, transcriptomic and proteomic technologies significantly contributed to characterize and better understand the human sperm at the molecular level (Jodar et al, 2012;Kovac et al, 2013;Amaral et al, 2014a). However, metabolomics, the study of small and low molecular weight molecules that are products of metabolism, has not been greatly applied in the study and characterization of human sperm cells (Kovac et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the metabolites and proteins as main determinants of the expression of the genomes and transcriptomes as also influenced by environmental cues, represents a first step to understand the normal composition and physiology of cells and tissues and their dysfunction associated with pathological states (Jodar et al, 2012;Wishart et al, 2013;Castillo et al, 2014a,b). In the case of the human spermatozoon, over 6000 proteins have been identified using mass spectrometry (MS), representing about 80% of the estimated proteome of this cell (Oliva et al, , 2009Amaral et al, 2013Amaral et al, , 2014aBaker et al, 2013;Azpiazu et al, 2014). However, and in *Correction added on 26 May 2015, after first online publication: article title corrected.…”
Section: Introductionmentioning
confidence: 99%
“…The defects leading to asthenozoospermia are not understood, which needs to change, to allow for innovative treatment options directed at the root cause of this problem. Mature sperm are believed to be transcriptionally and translationally silent (1), which demands proteomic studies (as opposed to genomic or transcriptomic studies) to understand the underlying pathways giving rise to sperm motility.…”
mentioning
confidence: 99%
“…The possibility is now open to further investigation of the molecular mechanisms within the sperm cell through which TBBPA exposure results in the detected effects. Different studies have demonstrated the presence of changes in the sperm proteome in infertile patients linked to protamine imbalances and DNA fragmentation (de Mateo et al, 2007;Martinez-Heredia et al, 2008;Oliva et al, 2008;Amaral et al, 2014). Therefore, important future extensions of our present work will be to explore in detail the overall sperm proteome and epigenome in TBBPA-exposed animals and their offspring, with the potential to provide additional important clues onto the mechanisms involved in the detected alterations.…”
Section: Discussionmentioning
confidence: 85%